Experimental investigation of full-culm bamboo tubes strengthened by filled concrete and bamboo sheets under axial compression. (January 2022) - Nie, Yuhan; Wei, Yang; Miao, Kunting; Zhao, Kang; Huang, Linjie
Abstract: To solve the problem of low compressive bearing capacity for the full-culm bamboos caused by their radial gradient variation and limited wall thickness, a new method, in which the concrete was filled inside the cavities of bamboo tubes and the bamboo sheets were wound onto the bamboo tubes with epoxy resin adhesive, was proposed in this paper to improve the behavior of full-culm bamboo structural members. The failure modes, ultimate bearing capacity of full-culm bamboo tubes with or without nodes, concrete-filled full-culm bamboo columns (CBs) and bamboo sheet-strengthened concrete-filled full-culm bamboo tubes (BSCBs) were investigated. Finally, the ultimate bearing capacity prediction method for CBs and BSCBs was studied based on the existing typical FRP-confined concrete columns. The results showed that the existence of bamboo nodes in the full-culm bamboo tubes may result in a decrease in the bearing capacity. In particular, the ultimate stress of specimens with relatively larger diameters and without nodes can be increased by a maximum of 18.2% compared to tubes with bamboo nodes. The ultimate bearing capacity of the full-culm bamboo tubes can obviously be increased using the scheme of filling concrete internally and strengthening by bamboo sheets externally. The average ultimate bearing capacity of CBs can be increased by a maximum of 65.3% compared with the corresponding full-culm bamboo tubes, and the average ultimate bearing capacity of BSCBs is at most 2.51 times higher than that of corresponding CBs. Although the bamboo tube and concrete cannot simultaneously reach the ultimate bearing capacity due to a certain difference in terms of their mechanical properties, such as the peak strain and elastic modulus, the ultimate bearing capacity of CBs and BSCBs can be predicted accurately using some existing typical strengthening models in terms of FRP-confined concrete columns. Highlights: New method for improving the bearing capacity of full-culm bamboo tubes was proposed. Effects of bamboo node, filled concrete and strengthened bamboo sheets on bamboo tubes were investigated. Ultimate bearing capacity of CBs and BSCBs was investigated. Methods for calculating the ultimate bearing capacity of CBs and BSCBs were proposed.